Effect of Operation Condition on Gelugur Acid (Garcinia atroviridis) Drying Rate Using Tray Dryer - R Hasibuan; Heri Gusman (Talenta Conference Series: Science and Technology (ST), 2018)
Garcinia atroviridis is a commodity with promising economic potential in the future, that it is not only used as spices but also as a necessity in cosmetic industry. One of the backgrounds of this research was the abundant amount of Garcinia atroviridis in North Sumatra. The post-harvest of processing Garcinia atroviridis was conducted by conventional drying process, i.e. drying out directly under the scorching sun where it was put on the sack or tarp and in the roads passed by motor vehicles. It had some disadvantages such as, a long drying time, lack of hygiene, contamination of dust and sand, animals and insects plague, as well as uncertain whether circumstances. Therefore, the dryer is very much needed as it can overcome these weaknesses. This research attempted to conduct a drying study of Garcinia atroviridis using tray dryer. It consisted of a drying room equipped with a tray of dried material, air heater, fan, control panel of temperature gauge and relative humidity (RH). The main purpose of this research was to study the influence of operating conditions against the rate of drying and characteristics of drying Garcinia atroviridis. This research was conducted by varying the drying temperature (45 and 55 oC) and air flow rate (1.15 and 2.25 m/s), with a weight of 500 grams Garcinia atroviridis. The drying was done by weighing each ingredient in a specified time interval until reaching constant weight. The results showed that the air flow rate and temperature affected the drying rate, where the 55 oC temperature and 2.25 m/s flow rate could lower the moisture content of 90% within 540 minutes. As for the characteristics of the drying Garcinia atroviridis, it generally showed that there were only two stages of drying rate, namely rising and declining drying rate. But on the operating conditions of the 1.15 m/s air flow rate and 55 oC temperature, it showed three stages namely, rising, constant and declining drying.